Financial market implications of the Federal debt paydown - Michael J. Fleming (Federal Reserve Bank of New York, 2001)
U.S. Treasury securities fill several crucial roles in financial markets: they are a risk-free benchmark, a reference and hedging benchmark, and a reserve asset to the Federal Reserve and other financial institutions. Many of the features that make the Treasury market an attractive benchmark and reserve asset are likely to be adversely affected by the paydown of the federal debt, and recent developments suggest that this may be happening already. Market participants are responding by moving away from Treasuries as a reference and hedging benchmark toward agency debt securities, corporate debt securities, and interest rate swaps. The Federal Reserve is taking steps to adjust its portfolio and should be able to do so with minimal implications for monetary policy.
Keywords: H63; G14; E52; G12; E43; 330; Treasury market; benchmark; reserve asset; liquidity; Schatzpapier; Öffentliche Schulden; Gesamtwirtschaftliche Liquidität; Finanzmarkt; Wertpapieranalyse; USA